2012
DOI: 10.2174/138945012803530026
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Involved in Cancer Development and Cell Fate Determination

Abstract: The possible physiological significance of long non-coding RNAs (lncRNAs) has only recently been recognized. Technical innovations such as the super high-resolution tiling array and deep sequencing technology have indicated their importance. It has been proposed that lncRNAs such as HOTAIR are involved in the recruitment of chromatin modifiers to the target genes. The lncRNA ANRIL has been reported to be associated with a Polycomb complex, recruiting it to the target gene INK4 locus where it suppresses transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…[20][21][22] This group of RNAs modulates gene expression through multiple mechanisms, such as epigenetics, alternative splicing, small RNA sponging as well as transcriptional and translational regulation. [23][24][25][26] Accumulating studies have shown that lncRNAs are involved in the regulation of autoimmunity-and inflammation-related processes, including nuclear factor-κB and Toll-like receptor signalling, cytokine expression, and immune cell proliferation and differentiation.…”
Section: -16mentioning
confidence: 99%
“…[20][21][22] This group of RNAs modulates gene expression through multiple mechanisms, such as epigenetics, alternative splicing, small RNA sponging as well as transcriptional and translational regulation. [23][24][25][26] Accumulating studies have shown that lncRNAs are involved in the regulation of autoimmunity-and inflammation-related processes, including nuclear factor-κB and Toll-like receptor signalling, cytokine expression, and immune cell proliferation and differentiation.…”
Section: -16mentioning
confidence: 99%
“…LncRNA is defined as a non-protein-coding RNA molecule longer than 200 nucleotides in length (7,8). In past decades, these long non-coding transcripts were simply considered as transcriptional 'noise' or cloning artifacts (9).…”
Section: Introductionmentioning
confidence: 99%
“…NF-Y directly binds to and activates the promoter of the pro-apoptotic gene, FAS cell surface death receptor (FAS) (13). Most lncRNAs involved in transcriptional regulation function as recruiters for transcriptional regulators such as polycomb proteins (14,15). However, PANDA does not function as a recruiter but as a repressor of NF-YA.…”
mentioning
confidence: 99%